Duration of the conditioning phase affects the results of plant-soil feedback experiments via soil chemical properties - Lepinay, Clémentine; Vondráková, Zuzana; Dostálek, Tomáš; Münzbergová, Zuzana (Oecologia, 2018)
Plant-soil feedback (PSF) is a fundamental mechanism explaining plant community composition. Two-phase experiments, i.e., conditioning and feedback, represent a common methodology to study PSF. The duration of the conditioning phase varies among studies and the PSF observed is often explained by its biotic component. Little is known about the temporal variation of PSF and its abiotic component. As early life stages are crucial for plant establishment, we grew Rorippa austriaca in soil conditioned over 2, 4, 6 or 8 weeks by a conspecific or a co-occurring species, Agrostis capillaris. For each conditioning duration, we analysed the soil chemical properties and the direction and intensity of intra- or inter-specific feedbacks. With increasing duration, the negative intra- and inter-specific feedbacks became stronger and weaker, respectively. The inter-specific feedback was more negative than the intra-specific feedback at 2 weeks and this reversed thereafter. The Mg content decreased with conditioning duration whatever the conditioning species was. With increasing duration, conditioning by R. austriaca strongly decreased pH, while A. capillaris did not affect pH. The K and P contents were not affected by the conditioning duration and were higher in R. austriaca soil than in A. capillaris soil. Our results suggest that not only conditioning species but also duration of conditioning phase may affect the magnitude of PSF. The changes in soil chemical properties linked to the conditioning species or the conditioning phase duration may drive the feedbacks by affecting plant growth directly or via the interacting microbial communities.
Keywords: rostliny; Plants; Plant Development; půda; Feedback; Soil Microbiology; zpětná vazba; půdní mikrobiologie; Soil; vývoj rostlin